MCDM/A studies for economic development, social cohesion and environmental sustainability: introduction - Pérez-Gladish, B.; Ferreira, F.; Zopounidis, C. (International Journal of Sustainable Development & World Ecology, 2021)
Exponential increase in economic activity and high levels of consumption have hindered longterm planning and made the sustainable management across different areas more difficult. Given this context, decision problems have been complicated by an ever-greater degree of complexity, forcing decision makers to seek out new approaches and methodologies that facilitate the processes that support decision-making. MCDM and MCDA are now well-known acronyms for multiple-criteria decision-making and multiple-criteria decision analysis, respectively. Due to MCDM/A methods’ exponential growth over the past few years, this special issue sought to bring together recent developments and methodological contributions within MCDM/A for economic development, social cohesion and environmental sustainability. All contributions relate to the 2030 Agenda for Sustainable Development, and were selected based on the way they relate to the Agenda’s sustainable development goals (SDGs).